Performance evaluation of node density-based adaptive routing scheme for disruption tolerant networks. (21st May 2008) - Chuah, Mooi-Choo; Yang, Peng
Traditional ad hoc routing protocols do not work in intermittently connected networks since end-to-end paths may not exist. In our earlier paper, we have evaluated a combined multihop, and message ferrying approach where special nodes are deployed as message ferries. Thus, in this paper, we design a node-density based adaptive routing scheme where regular nodes volunteer to be message ferries when there are very few nodes around them to ensure the feasibility of continued communications. Our simulation results indicate that our scheme can achieve the best delivery ratio in very sparse ad hoc networks that are prone to frequent disruptions.